Incidencia del material de reciclaje en el desarrollo de la capacidad de aprendizaje de los niños de educación inicial de la Unidad Educativa Francisco Huerta Rendón de la ciudad de Babahoyo - Lavayen Bejarano, Ruby Stefania (2022)
Incidence of recycling material in the development of the learning capacity of children in initial education of the Francisco Huerta Rendon Educational Unit in the city of Babahoyo. Environmental awareness is based on recycling products that can be reused for teaching children beginning in addition to teaching what products can be reused for fun. Increasing the retention capacity of what is learned in class hours and at the same time teaching in their homes the values about caring for the planet using recycled products, considering that the planet deteriorates every day by perforating the ozone layer and increasing the greenhouse effect which it is the cause of extreme heat or extreme climate change that will extinguish the lives of human beings. The economic situation in our country has caused the unemployment rate to increase, which does not allow parents to buy what is necessary for their children to learn from their homes. Young children's learning is based on the stimulation of the senses and the imagination that are strengthened by the materials they have in their environment. The general problem is: How does the use of recycled materials affect learning in the didactic resources of the children of initial education of the Educational Unit "Francisco Huerta Rendon"?, applying collection techniques such as the survey towards the teachers to find Findings that provide a solution to the main general problem.